2014
DOI: 10.4161/cc.29272
|View full text |Cite
|
Sign up to set email alerts
|

Dexamethasone-induced autophagy mediates muscle atrophy through mitochondrial clearance

Abstract: Glucocorticoids, such as dexamethasone, enhance protein breakdown via ubiquitin-proteasome system. However, the role of autophagy in organelle and protein turnover in the glucocorticoid-dependent atrophy program remains unknown. Here, we show that dexamethasone stimulates an early activation of autophagy in L6 myotubes depending on protein kinase, AMPK, and glucocorticoid receptor activity. Dexamethasone increases expression of several autophagy genes, including ATG5, LC3, BECN1, and SQSTM1 and triggers AMPK-d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

6
57
0
1

Year Published

2016
2016
2019
2019

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 95 publications
(64 citation statements)
references
References 67 publications
6
57
0
1
Order By: Relevance
“…Moreover, muscle mfn2 protein levels were repressed in several catabolic conditions [62][63][64][65]. Lokireddy et al showed that Dex increased mfn2 degradation in myotubes [66], and Liu et al found that Dex decreased mfn2 levels in the TA muscles of mice [12], while Troncoso et al reported that Dex had no influence on mfn2 expression in myotubes [67]. Our results suggested that Dex significantly decreased mfn2 expression levels in skeletal muscle both in vivo and in vitro.…”
Section: Discussionmentioning
confidence: 43%
“…Moreover, muscle mfn2 protein levels were repressed in several catabolic conditions [62][63][64][65]. Lokireddy et al showed that Dex increased mfn2 degradation in myotubes [66], and Liu et al found that Dex decreased mfn2 levels in the TA muscles of mice [12], while Troncoso et al reported that Dex had no influence on mfn2 expression in myotubes [67]. Our results suggested that Dex significantly decreased mfn2 expression levels in skeletal muscle both in vivo and in vitro.…”
Section: Discussionmentioning
confidence: 43%
“…This suggests a regulatory role for mitochondrial fission in mitochondrial quality control in skeletal muscles via activation of autophagy (Troncoso et al. ). Mitochondrial dynamics also play a significant role in the myogenic differentiation of myoblasts.…”
Section: Divergent Effects Of Mdivi‐1 On Cell Survivalmentioning
confidence: 99%
“…Mitophagy is controlled by various factors and the signalling pathways involved are extremely complicated. It was research has shown that under the stimulation of free radicals, the mitochondrial fission protein Drp1 (dynamin-related protein-1) mediated a tubular mitochondrial split into punctate mitochondria (Troncoso et al, 2014). This dynamic process is necessary for the occurrence of mitochondrial autophagy and plays a vital role in neurodegenerative disease (Saez-Atienzar et al, 2014).…”
Section: Introductionmentioning
confidence: 99%